2002
DOI: 10.1126/science.1074111
|View full text |Cite
|
Sign up to set email alerts
|

Splay Fault Branching Along the Nankai Subduction Zone

Abstract: Seismic reflection profiles reveal steeply landward-dipping splay faults in the rupture area of the magnitude (M) 8.1 Tonankai earthquake in the Nankai subduction zone. These splay faults branch upward from the plate-boundary interface (that is, the subduction zone) at a depth of approximately 10 kilometers, approximately 50 to 55 kilometers landward of the trough axis, breaking through the upper crustal plate. Slip on the active splay fault may be an important mechanism that accommodates the elastic strain ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
588
2
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 555 publications
(616 citation statements)
references
References 19 publications
23
588
2
3
Order By: Relevance
“…• It is geographically coincident with the updip termination of slip during the 1944 Tonankai event, as inferred from tsunami (Tanioka and Satake, 2001) and seismic (Kikuchi et al, 2003) waveform inversions, and recent structural studies indicate that it may have experienced coseismic slip (e.g., Park et al, 2002).…”
Section: Background Geological Settingmentioning
confidence: 89%
See 2 more Smart Citations
“…• It is geographically coincident with the updip termination of slip during the 1944 Tonankai event, as inferred from tsunami (Tanioka and Satake, 2001) and seismic (Kikuchi et al, 2003) waveform inversions, and recent structural studies indicate that it may have experienced coseismic slip (e.g., Park et al, 2002).…”
Section: Background Geological Settingmentioning
confidence: 89%
“…A significant, laterally extensive fault system (the "megasplay" fault; Park et al, 2002) slips in discrete events that may include tsunamigenic slip during great earthquakes. During the interseismic period, the megasplay remains locked and accumulates strain.…”
Section: Overview Of the Nantroseize Complex Drilling Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining swath-bathymetry and seismic reflection data has demonstrated a causal relationship between splay-fault behavior and seafloor lineament topography in segment C, i.e., the 1944 Tonankai earthquake rupture area (Park et al, 2002). Many 2-D and 3-D seismic re ection data (Park et al, 2003(Park et al, , 2010Moore et al, 2007) have revealed a steeply landward-dipping splay-fault system in segment C, e.g., line 4 in Fig.…”
Section: Swath-bathymetry Data and Their Interpretationmentioning
confidence: 98%
“…In particular, the Nankai subduction zone off Kii Peninsula (Fig. 1) is characterized by steeply landward-dipping megasplay faults (Park et al, 2002;Moore et al, 2007) in the rupture area of the 1944 Tonankai (M 8.1) earthquake. This megasplay fault branches upward from the plate interface (i.e., the megathrust fault), breaking through the overlying accretionary wedge.…”
Section: Introductionmentioning
confidence: 99%